THE AFTERMATH OF MARKETING MIX ON DECISIONS CONSUMER PURCHASES FROM TRADING COMPANIES (Case Study at “UD. MAJU” in Surabaya) - Mahjudin Mahjudin; Ignatius Donny Antonius Saputra; Achmad Daengs GS (PT. Mawadaku Sukses Solusindo, 2024)
Companies that implement a quality management system within their company are organization, customer and market oriented, by combining the search for existing facts and problem solving. Companies should not only sell their products, but must know consumers' needs and desires. Knowledge of consumer behavior is essential to good marketing practices. Satisfaction in marketing should start by carrying out an analysis of consumer behavior in the right situation. This will at least encourage company managers to carry out what marketing activities should be proposed, planned and carried out. Therefore, companies must have tools in their marketing which are more commonly referred to as marketing mix which includes product, price, location and promotion. This research uses primary data, namely data obtained directly from respondents' answers by distributing questionnaires and secondary data, namely data obtained from the company that is used as the object of research. The analysis technique used in this research is multiple linear regression analysis. Meanwhile, the statistical test uses the F test and t test. The research results obtained using the SPSS program with the results of multiple linear regression analysis obtained by the F test show that there is a significant influence between the independent variable and the dependent variable with the calculated F value (22.573) > F table (2 .50). For the t test, it can be seen that the product variable (X1) has a significant influence on consumer purchasing decisions (Y) with a calculated t value (3.728) > t table (1.9944), the price variable (X2) has a significant influence on purchasing decisions consumer (Y) with a calculated t value (4.072) > t table (1.9944), the location variable (X3) has a significant influence on consumer purchasing decisions (Y) with a calculated t value (3.080) > t table (1.9944), while the promotion variable (X4) has a significant influence on consumer purchasing decisions (Y) with a calculated t value (3.230) > t table (1.9944).